HUBUNGAN MOTIVASI INTRINSIK DAN MOTIVASi EKSTRINSIK DENGAN HASIL BELAJAR (INDEKS PRESTASI) MAHASISWA TINGKAT II AKADEMI KEBIDANAN ANUGERAH BINTAN TANJUNGPINANG TAHUN 2017 - Putri, Hanny Hernadha; Utami, Risqi (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
In terms of teaching and learning activities, motivation leads the students to the learning achievement or outcomes, whereas on the other hand, the Competency Test for Midwives set as a benchmark or standart of the midwifery education quality. It Anugerah Bintan Midwifery Academy these past three years that there was a diminishing point on the results as noted sequentially 69.80%, 86.63%, and 72.15%. Therefore, this study aims to determine wether there is a correlation associated to the intrinsic and extrinsic motivations with the studentsâ€™ learning outcomes. For the research design, the researchers select an analitycal survey of cross sectional approach. By employing the total sampling technique, the population of this study respondents in total. This study lasted six months from February to August 2017. The data were collected by distributing the questionnaires to the respondents and the academic transcript of students were also used to fortify. Afterwards, the data gatheredÂ  was analyzed by Chi-Square statistical test. The result of the study shows that 68.9% of students were intrinsically motivated and 62.2% of them were extrinsically motivated with 66.7% met the learning outcomes satisfaction. It is ensued that there is a correlation between the intrinsic motivation and the learning outcomes with (p value = 0.000) and (p value = 0,000) for the extrinsic motivation and the learning achievement of students. Based on these findings, it can be concluded that there is a significant correlation between both intrinsic and extrinsic motivations to the learning outcomesor achievements of second grade-student of Anugerah Bintan Midwifery Academy of Tanjungpinang in 2017. Finally, for future researchers, it is suggested to be able to enlarge and optimize more both the intrinsic and extrinsic motivations.